SCHOOL ORGANIZATIONAL CULTURE; FORMAL INSTUTIONS CEREMONIAL IN FORMING STUDENT CHARACTER EDUCATION - Hartatik, Dewi; Siswanto, Romi (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
AThe purpose of this article is to discuss the form of school culture in instilling character education values for students at SMAN I Kalianget Sumenep. This research method uses descriptive qualitative. Data collection was obtained from the process of observation and mandala interviews. Then the data were analyzed by condensing data, presenting data, and drawing conclusions. The findings of this study are that the inculcation of character education at SMAN I Kalianget is through school culture such as congregational midday prayers, daily worship checklists, cleaning classes and mosques, getting used to permission before leaving class, flag ceremony, Friday alms, extra Saturdays (extracurricular activities). which is held every week through exemplary activities created based on the school's vision and mission. Of course, with the values of character education formed from the organizational culture, students can be emotionally and morally intelligent.